Stable π-radical nanoparticles as versatile photosensitizers for effective hypoxia-overcoming photodynamic therapy. Issue 2 (19th November 2020) - Cui, Xiao; Lu, Guihong; Dong, Shengzhi; Li, Shengliang; Xiao, Yafang; Zhang, Jinfeng; Liu, Yanhong; Meng, Xiangmin; Li, Feng; Lee, Chun-Sing
Abstract : A stable π-radical is used as a photosensitizer for photodynamic therapy. Under hypoxic conditions, sufficient O2 − ˙ generation and cytotoxicity were observed addressing the most important hurdle for successful PDT in a tumor microenvironment. Abstract : We report the first demonstration using a stable π-radical as a versatile photosensitizer for hypoxia-overcoming photodynamic therapy. After self-assembling the radical molecules into radical nanoparticles (NPs), the NPs show good water dispersibility, good biocompatibility, broad near-infrared (NIR) absorption and emission at ∼800 nm. Significantly, the radical NPs remain stable in various biological mediums, after 100 days exposure to the ambient environment, and even after long-term laser irradiation, which is superior to many reported radical-based materials. More importantly, upon 635 nm laser irradiation, sufficient superoxide radical (O2 − ˙) generation and in vitro cytotoxicity were observed addressing the most important hurdle for successful PDT in the oxygen-deficient tumor microenvironment. In addition, the radical NPs are also demonstrated to have effective in vivo PDT efficacy, and excellent biosafety.